(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Extra-articular distal tibia fractures pose significant surgical challenges given the unique anatomy of the metaphyseal-diaphyseal junction and the limited soft tissue envelope surrounding the distal leg. Two widely practiced surgical techniques, locking compression plate (LCP) fixation and intramedullary nailing (IMN), have both demonstrated effectiveness, yet continue to be debated regarding perioperative morbidity, radiological outcomes, and functional recovery. Objectives: To compare LCP and IMN in terms of operative parameters, time to radiological union, functional recovery assessed by the American Orthopaedic Foot and Ankle Society (AOFAS) and Olerud-Molander Ankle Score (OMAS), and postoperative complications. Methods: This prospective observational study enrolled 150 patients aged 18–70 years with extra-articular distal tibia fractures (AO/OTA type 43-A) treated at a tertiary care centre in Dindigul, Tamil Nadu, between January 2024 and January 2026. 80 Patients were managed with LCP and 70 with IMN. Outcome measures included operative time, estimated blood loss, hospital stay, fluoroscopy exposure, time to union, functional scores, alignment, and complications. Results: IMN demonstrated significantly shorter operative time (74.2 ± 14.3 vs 98.4 ± 18.6 min, p<0.001), reduced blood loss (124.4 vs 182.6 mL, p<0.001), and shorter hospital stay (5.8 vs 7.6 days, p<0.001). Time to radiological union was shorter with IMN (16.4 vs 18.2 weeks, p=0.003). Mean AOFAS (85.1 vs 82.4, p=0.04) and OMAS (83.2 vs 79.6, p=0.02) scores were superior in the IMN group. On categorical functional grading, IMN yielded more excellent outcomes (27.1% vs 17.5%) and fewer fair/poor outcomes (10.0% vs 15.0%), though the overall distribution did not reach statistical significance (p=0.23). Combined excellent/good outcomes were 90.0% in IMN vs 85.0% in LCP (p=0.31). Complication rates were comparable between groups (34.3% vs 32.5%, p=0.81), though wound complications were more frequent with LCP and anterior knee pain was specific to IMN. Conclusion: Both techniques provide satisfactory fixation for extra-articular distal tibia fractures. IMN offers advantages in perioperative morbidity and functional recovery, while LCP provides better coronal alignment control in multifragmentary patterns. Surgical decision-making should be individualised based on fracture morphology and the local soft tissue envelope.